Phonetic and phonological influence of a speech-Impaired speaker on Rhythm - Chhina, Gurnikaita; Yoon, Tae-Jin; Humphreys, Karin (Canadian Acoustics, 2011)
A study showing a detailed phonetic analyses of a 61 year-old monolingual female English speaker is presented. There is considerable variability among reported cases of FAS in terms of phonetic characteristics and impairments. The speaker, LA, is a monolingual English-speaking Canadian Woman and she was 61-year old when the data were collected. One day three years after the accident, her family member observed noticeable changes in her speech such as word searching, stuttering, and a robotic style of speech. Upon request by the family members, the third author visited the speaker and collected the speech recordings through sessions with the patient The collected recordings range from simple read sentences to passages, and to spontaneous description of pictures. Typical stress-timed languages such as English have complex syllable structure and tend to have reduced vowels in unstressed positions.